Evaluasi Saluran Drainase Jalan Wolter Monginsidi Passo Kecamatan Baguala Kota Ambon - Syafna Maruapey; Renny James Betaubun; Juvrianto Chrissunday Jakob (KOLONI, 2024)
In general, drainage is defined as a series of water structures that reduce and remove excess water from an area or land so that the land can function optimally. If drainage is problematic, it will result in puddles on the highway's surface. One of the highways that experience inundation due to problematic drainage is Wolter Monginsidi Street in Passo, Baguala District, Ambon City. The old drainage is damaged and the channel dimensions are small. So that the drainage channel is remade on the road. The old drainage channel is 894 m long, 78 cm wide and 76 cm high. In comparison, the new existing drainage channel has a length of 894 m, a width of 120 cm, and a height of 120 cm using 16-20 mm reinforcement. Therefore, it is necessary to evaluate the drainage channel on Jalan Wolter Monginsidi Passo, Baguala District, Ambon City to determine the dimensions of the existing channel, population growth, and disposal of household sewage entering the drainage channel and runoff discharge on the highway. Based on the calculation, the number of residents in the 10th year (the year 2032) is as many as 1,165 people, with the amount of discharge water (Qb) = 0, 00023283 m3 / s / ha, runoff discharge (Qr) = 0.00467 m3 / s, channel discharge (Qs) = 2.796480 m3 / s with a difference of 2.791783 m3 / s. So that the capacity of the drainage channel meets and is feasible to use